2007
DOI: 10.1021/bi700935z
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Solution Structure of Human Deoxyhemoglobin in the Absence and Presence of an Allosteric Effector

Abstract: We present a nuclear magnetic resonance (NMR) study in solution of the structures of human normal hemoglobin (Hb A) in the deoxy or unligated form in the absence and presence of an allosteric effector, inositol hexaphosphate (IHP), using 15 N-1 H residual dipolar coupling (RDC) measurements. There are several published crystal structures for deoxyhemoglobin A (deoxy-Hb A), and it has been reported that the functional properties of Hb A in single crystals are different from those in solution. Carbonmonoxyhemogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 46 publications
1
37
0
Order By: Relevance
“…The experimentally determined RDC values can be well reproduced by calculations based on either of the X-ray structures for isolated α- or β-chain or that of an isolated αβ dimer. However, a larger χ 2 value is obtained when based on the whole tetramer (39, 57). For HbCO A, a better fitting is obtained by a rotation of one αβ dimer with respect to the other (57).…”
Section: Discussionmentioning
confidence: 96%
“…The experimentally determined RDC values can be well reproduced by calculations based on either of the X-ray structures for isolated α- or β-chain or that of an isolated αβ dimer. However, a larger χ 2 value is obtained when based on the whole tetramer (39, 57). For HbCO A, a better fitting is obtained by a rotation of one αβ dimer with respect to the other (57).…”
Section: Discussionmentioning
confidence: 96%
“…Gray and Gibson (24) observed a kinetic difference between the R-and ·-chains of Hb induced by IHP binding. Recently, a study from our laboratory based on RDC measurements has shown that IHP causes changes mainly in the tertiary structure of deoxy-Hb and mostly in the ·-subunit (11). These observations show that in general, IHP can affect the two types of subunits of Hb A differently.…”
Section: Ihp Affects R-and ·-Subunits Of Hbco a Differentlymentioning
confidence: 94%
“…71-72 The calculated RDCs 72 were obtained from eight crystal structures of deoxy-Hb A, 4HHB, 1HGA, 1KD2, 1RQ3, 1XXT, 1BZ0, 2DN2, and 1YHR. The scatter in the eight correlation plots between the observed and calculated RDCs is larger than the experimental precision.…”
Section: Structurementioning
confidence: 99%
“…(iii) Allosteric effectors, e.g., IHP, alter both the tertiary and quaternary structure of deoxy- and CO-Hb as well as the dynamics of the Hb molecule, thus affecting its ligand affinity. 70-72,74 (iv) RDC measurements of Hb A in different aqueous liquid crystalline media and at several magnetic field strengths have shown that in solution, the quaternary conformations for both the CO- and deoxy-forms of Hb A are different from their crystal structures and both exist as dynamic ensembles of various structures. 69-72 It is tempting to speculate that the various T- and R-type structures reported by crystallographers (Table 1) may be the so-called “pre-existing protein conformations” and represent some of the conformational ensembles detected by our NMR measurements.…”
Section: Dynamic and Structural Basis Of Hemoglobin Allosterymentioning
confidence: 99%